Differential Transcription and Alternative Splicing in Cotton Underly Specialized Defense Responses Against Pests - Chen, Dian-Yang; Chen, Qiu-Yi; Wang, Dan-Dan; Mu, Yu-Pei; Wang, Mu-Yang; Huang, Ji-Rong; Mao, Ying-Bo (Frontiers in Plant Science, 2020)
The green mirid bug (Apoygus lucorum) and the cotton bollworm (Helicoverpa armigera) are both preferred to living on cotton but cause different symptoms, suggesting specialized responses of cotton to the two insects. In this study, we investigated differential molecular mechanisms underlying cotton plant defenses against A. lucorum and H. armigera via transcriptomic analyses. At the transcription level, jasmonate (JA) signaling was dominated in defense against H. armigera whereas salicylic acid (SA) signaling was more significant in defense against A.lucorum. A set of pathogenesis-related (PR) genes and protease inhibitor genes were differentially induced by the two insects. Insect infestations also had an impact on alternative splicing (AS), which was altered more significantly by the H. armigera than A.lucorum. Interestingly, most differential AS (DAS) genes had no obvious change at the transcription level. GO analysis revealed that biological process termed “RNA splicing” and “cellular response to abiotic stimulus” were enriched only in DAS genes from the H. armigera infested samples. Furthermore, insect infestations induced the retained intron of GhJAZs transcripts, which produced a truncated protein lacking the intact Jas motif. Taken together, our data demonstrate that the specialized cotton response to different insects is regulated by gene transcription and alternative splicing as well.